TOEFL test of English as a foreign language = Chương trình luyện thi TOEFL mới NTC's preparation - Broukal, Milada; Woods, Enid Nolan; First News (Tp.HCM : Nxb Trẻ, 1999)
Preparation for TOEFL is geared toward anyone taking the TOFLE (those preferably with a score of 400 upwards). It is designed for both self-study and classroom use.
Keywords: English language; TOEFL; English language